Environmental Indemnity: Seeking Effective Mechanisms for Ensuring the Participation of Law Enforcement Agencies - ALIBAYEV, Askar Kanatovich; BEKISHEVA, Sabigul Dzhanabayevna; HERNÁNDEZ GARCÍA, Judith Josefina; CHUMACEIRO HERNÁNDEZ, Ana Cecilia; IBRAYEV, Alisher Serikbolovich (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).25, 2022)
Currently, there is an increase in the number of environmental violations and the environmental damage they cause. The article presents the results of the study of the legal framework and the practice of law enforcement to determine environmental damage, its scope, and possible compensation. The objective is to define the powers, functions, and roles of the agencies responsible for enforcing the law to guarantee environmental compensation. It is studied from the bibliographical, analytical, and critical review of the legal regulation, the practice of applying the law, and the scientific opinions on the compensation for damage to the environment. It is concluded that adequate environmental compensation depends directly on the activities of law enforcement agencies to identify and suppress environmental crimes and carry out administrative or criminal proceedings against offenders. The particularities of filing a civil lawsuit as a tool to repair the damage caused by an environmental crime are considered, focused on organizational and legal issues that negatively affect the effectiveness of environmental rights protection, as mentioned above, including the environmental incompetence of those who investigate crimes in that sphere and the shortcomings of judicial practice in determining the environmental damage. The main mechanisms to ensure the participation of law enforcement agencies in the calculation of environmental compensation, which has been developed in world practice, are presented. The authors made proposals for improving the existing organizational and legal framework and leveling the shortcomings of law enforcement practice.